TOXICITY OF SOME HOUSEHOLD PRODUCTS ACCORDING TO PHYTOTESTING WITH LEPIDIUM SATIVUM L. - Tkachuk, Наталія; Zelena, Любов (Biota. Human. Technology, 2023)
Information on the toxicity by the phytotest with Lepidium sativum L. for perfumed paper napkins and some synthetic detergents for children’s underwear (in particular, phosphate-free powder), which are widely used in everyday life, is not available. The aim of this study was to investigate the toxicity of some household products (perfumed paper napkins and synthetic detergents for children’s underwear) according to the growth test with L. sativum. Methodology. 2 types of perfumed paper napkins and 3 types of synthetic detergents for children’s underwear (with concentrations of aqueous solutions of 0.05 % and 0.1 %) produced in Ukraine were studied. The research was carried out by the well-known method of phytotesting using L. sativum as a test plant (producer of seeds is Svityaz LLC, Ukraine), in which germination energy was determined on the 3rd day, germination and biometric and morphometric parameters (root length and above-ground part) on the 5th day. Based on the obtained results, phytotoxic indexes were calculated – the seed germination index and the root length index. The results were processed statistically. Scientific novelty. For the first time, a phytotest with L. sativum showed the absence of toxicity in perfumed paper napkins and extreme and moderate toxicity, depending on the concentration and type, in the investigated synthetic detergents for washing children’s underwear. The need to pay attention to the presence in the composition, in addition to other compounds, of plant growth stimulants, which can mask the toxicity of the investigated solutions in growth phytotests, is noted. Conclusions. It was established that the researched perfumed paper napkins do not show phytotoxicity (test indicators of L. sativum within the control values), and among the studied synthetic detergents for children’s underwear, the greatest toxicity according to the phytotest with L. sativum shows the phosphate-free powder for children’s underwear. Average toxicity at a concentration of 0.05 % (inhibition of the growth of seedling roots by almost 30 %) and extreme toxicity at a concentration of 0.1 % (inhibition of the growth of seedling roots by almost 100 %) was established for the investigated aqueous solution of phosphate-free powder. The absence of phytotoxic properties after treatment with conditioner-rinse containing aloe vera leaf juice indicates that it should be considered the presence of plant growth stimulants in the composition of the products, which can affect the result of the growth phytotest. According to the theoretical analysis of the toxic properties of the constituent compounds of the studied synthetic detergents and the results of the phytotoxicity study of the detergents, their potential negative impact on both human health and the state of the environment was established.